Flute Teaching Curriculum in Music University in China - Wu Yi; Khunthongchan, Prasert (Journal of Modern Learning Development, 2024)
The college flute teaching course is different from the professional teaching that mainly focuses on imparting knowledge. It is a practical and technical teaching approach. Its primary task is to teach students, under the guidance of correct ideas and methods, to gradually establish correct playing habits, gradually master the skills and rules of flute playing, and express the thoughts, feelings and connotation style of music works through their own learning and playing practice. The college flute teaching course, as an instrumental music subject, has a wide range of implications and influences, and is scientific, artistic, and creative. The so-called "scientificity" refers to exploring scientific teaching laws, researching scientific teaching methods, and conducting scientific skill training. "Artistic" means to cultivate students’ musical sense and understanding; Cultivate students’ desire for expression and artistic expression; Cultivate students’ comprehensive performance skills and artistic style. Creativity "refers to mobilizing students’ subjective creative consciousness and unleashing the originality of their performances. Through four years of professional learning, students will be able to proficiently master the basic theories and performance techniques of flute performance, possess the ability to comprehensively appreciate, analyze, and express works, and be able to perform works at intermediate level or above, as well as be competent in general solo, ensemble, and ensemble.